A CRITICAL ANALYSIS OF THE IMPLEMENTATION OF THE RIGHT TO EDUCATION IN THE CONSTITUTIONAL DEVELOPMENT OF PAKISTAN - Javed Ali Rajper; Mujeeb Rehman Khuhro; Shakeel Ahmed (International Journal of Contemporary Issues in Social Sciences, 2024)
Education in Pakistan is a luxury that most cannot afford. Without educating children, there is no hope for empowerment and progress. A state is obligated to specific duties towards its children. Along with the other basic rights of nationality, housing, recreation, freedom, protection, and belonging, the most significant of all is the provision of education (Tahera Hasan, 2022). The core objective of this study is to critically analyze the implementation of Right to Education in the Constitutional History of the Pakistan after independence. Therefore, in this study the Independence Act, 1947 till the 18th amendment in which article 25-A is inserted in the Islamic Republic of Pakistan 1973 are critically analyze for finding the enactment of the Right to Education. While, education played as a role of third eye for human being, in connection with this the various documents have been framed in the legal system of Pakistan, but huge gap still exists in the codified Constitution and laws, when we talk about its true spirit in letter and patent. Moreover, this study is only conducted from the available data and researchers have tried to conduct critically study over the measures taken by the government regarding implementation of the Right to Education. Furthermore, Article 37-b allows the state to promote social equity and eradicate socially unacceptable behaviors, such as eliminating illiteracy and providing free and mandatory education within the shortest practicable time frame.